PENERAPAN METODE STRUKTURAL ANALITIK SINTETIK DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN MURID KELAS I SD INPRES BONTOMANAI KECAMATAN TAMALATE KOTA MAKASSAR - Riskal Fitri (Fakultas Keguruan dan Ilmu Penidikan UIM, 2018)
The study aimed to describe the ability to read through the SAS method and to know the effectiveness of the application of the SAS method in improving the ability to read the beginning of the first grade students of SD Inpres Bontomanai, Tamalate District, Makassar City. This research is a class action research with 30 subjects as the first grade students. The data collection technique used uses test and observation techniques. The results showed that: the ability to read the first grade students of SD Inpres Bontomanai Makassar through the application of the SAS method can improve students 'reading comprehension based on the data obtained, namely the students' ability to read in the qualitative and quantitative aspects (average reading ability test results beginning), namely: cycle I in the sufficiently capable category with a value of 53.66, then increases to the category of being able to read the beginning of the second cycle with a value of 65.5.Keywords: Reading Beginning, SAS method